Antidepressant Use and Risk for Preeclampsia - Palmsten, Kristin (2013)
BACKGROUND: Prior studies suggest that women who use antidepressants during pregnancy have an increased risk for preeclampsia, yet the comparative safety of specific antidepressants remains unclear. US nationwide Medicaid Analytic eXtract (MAX) data have not been used to study medication safety during pregnancy. METHODS: We identified 100,942 pregnant women with depression from 2000-2007 MAX data. We used pharmacy dispensing records to ascertain exposure to selective serotonin reuptake inhibitor (SSRI), serotonin-norepenephrine reuptake inhibitor (SNRI), tricyclic, bupropion, other antidepressant monotherapy or polytherapy, and specific antidepressants, during the second trimester and first half of the third trimester. Relative risks (RR) and 95% confidence intervals (CI) were adjusted for delivery year, preeclampsia risk factors, depression severity proxies, other antidepressant indications, other medications, and healthcare utilization. RESULTS: The risk of preeclampsia was 5.4% among women with depression and no antidepressant exposure. Compared with these women, the risk for preeclampsia was higher among those receiving SNRI (RR: 1.52, 95% CI: 1.26–1.83) and tricyclic monotherapy (RR: 1.62 95% CI: 1.23–2.12), but not SSRI monotherapy (RR: 1.00, 95% CI: 0.93–1.07) or other antidepressants. Compared with women receiving SSRI monotherapy, preeclampsia risk was higher among women with SNRI (RR: 1.54 95% CI: 1.28–1.86) and tricyclic (RR: 1.64 95% CI: 1.25–2.16) monotherapy. None of the specific SSRIs was associated with preeclampsia. The RR with venlafaxine was 1.57 (95% CI: 1.29–1.91) and with amitriptyline, 1.72 (95% CI: 1.24–2.40). CONCLUSIONS: In this population, SNRIs and tricyclics were associated with a higher risk of preeclampsia than SSRIs.